Twenty-Seven Years Experience With Transvenous Pacemaker Implantation in Children Weighing <10 kg. (February 2016) - Konta, Laura; Chubb, Mark Henry; Bostock, Julian; Rogers, Jan; Rosenthal, Eric
Abstract : Background—: Epicardial pacemaker implantation is the favored approach in children weighing <10 kg in many units. The high incidence of premature failure and fractures with earlier epicardial leads led our unit to undertake transvenous pacemaker implantation in neonates and infants from 1987. To date there have been no long-term follow-up reports of what is for many a controversial strategy. Methods and Results—: Between 1987 and 2003, 37 neonates and infants—median age 6.7 months (1 day to 3 years) and median weight 4.6 kg (2.7–10 kg)—had a permanent transvenous pacing system implanted. Pacing leads were placed into the right ventricular apex/outflow tract through a subclavian vein puncture with a redundant loop in the atrium. Three patients were lost to follow-up, 4 patients died from complications of cardiac surgery, and 2 patients had their system removed. At long-term follow-up in 28 patients at a median of 17.2 (range, 11.2–27.4) years, 10 patients have a single chamber ventricular pacemaker, 14 a dual chamber pacemaker, 3 a biventricular pacemaker, and 1 has a single chamber implantable cardioverter defibrillator. Subclavian vein patency was assessed in 26 patients. The overall subclavian vein occlusion rate was 10 of 13 (77%) <5 kg and 2 of 13 (15%) >5 kg during long-term follow-up. After a median of 14.3 (range, 13.4–17.6) years of pacing, 7 patients continue with their original lead. Conclusions—: Transvenous pacing in infants <10 kg results in encouraging short- and long-term clinical outcomes. Subclavian vein occlusion remains an important complication, occurring predominantly in those weighing <5 kg.